2015
DOI: 10.1186/s12889-016-2806-6
|View full text |Cite
|
Sign up to set email alerts
|

Absolute cardiovascular risk in a Fiji medical zone

Abstract: BackgroundThe population of Fiji has experienced emergence of non-communicable disease (NCD) and a plateau in life expectancy over the past 20 years.MethodsA mini-STEPS survey (n = 2765) was conducted in Viseisei in Western Fiji to assess NCD risk factors (RFs) in i-Taukei (Melanesians) and those of Indian descent aged 25–64 years (response 73 %). Hypertension (HT) was defined as systolic blood pressure (BP) ≥140 mmHg or diastolic BP ≥90 mmHg or on medication for HT; type 2 diabetes mellitus (T2DM) as fasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It generates success and creates valuable iTaukie role models for families and communities. Many studies reported that being Indigenous, iTaukie people are more likely to have natural athletic ability, which is already a significant aspect of Indigenous men’s lives [ 4 , 8 , 13 , 27 , 53 ]. ITakuie females in the rural community require specific attention when developing physical activity health promotion programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It generates success and creates valuable iTaukie role models for families and communities. Many studies reported that being Indigenous, iTaukie people are more likely to have natural athletic ability, which is already a significant aspect of Indigenous men’s lives [ 4 , 8 , 13 , 27 , 53 ]. ITakuie females in the rural community require specific attention when developing physical activity health promotion programs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the iTaukie community, as part of efforts to improve Indigenous health and wellbeing, suggests that this issue of physical activity be given attention [ 3 ]. Adults with high body mass index (BMI) are at risk for NCDs, including hypertension, stroke, cardiovascular diseases, diabetes, and multiple cancers [ 4 ]. Studies confirm daily exercise is an effective primary and secondary prevention measure to prevent NCDs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each study used a different definition of overweight and obesity and adopted different methodology, which impede an accurate estimation of period trends [6]. In 2002, the World Health Organisation (WHO) utilised the STEPS survey to report that 18% of the adult Fijian population was obese [6,7]. In 2013, using the same study, the prevalence of obesity was reported to be 30.6% [8].…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2002, the World Health Organisation (WHO) utilised the STEPS survey to report that 18% of the adult Fijian population was obese. 6,7 In 2013, using the same study, the prevalence of obesity was reported to be 30.6%. 8 The staple food of Indigenous Fijian people (known as iTaukei) has been influenced by global food transition, the adoption of a western lifestyle, which contributed to the epidemic of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…This limiting of participation to certain groups has wider consequences, such as the touted physical and mental benefits of sport, particularly in a nation like Fiji, beset with NCDs (Gyaneshwar et al, 2016), along with the social development opportunities associated with participation (Burnett 2006). But crucially, for this discussion, sport is complicit in maintaining an imagined distance between groups in a context that has struggled with the consequences of ethnic division (Robertson 2012).…”
Section: Sport and Ethno-racial Formation In Divided Societiesmentioning
confidence: 99%